The Origins of Roman Christian Diplomacy : Constantius II and John Chrysostom As Innovators - Stevenson, Walter (Taylor & Francis Group, 2021)
Cover -- Half Title -- Title Page -- Copyright Page -- Dedication Page -- Contents -- Preface -- 1 Approaching Roman Christian diplomacy in context -- Challenges to understanding: "religion" -- Challenges to understanding: "secular" -- Challenges to understanding: church and state -- Challenges to understanding: Constantine as symbol of Christian imperialism -- The case for Constantine's mission to the Goths -- Constantine's plan to Christianize Persia -- Other historiographical challenges -- Plan of the book -- 2 Mission to Himyar and Aksum in context -- Literary source one: Philostorgius narrates the story -- Excursus: the importance of the Indian Ocean trade route -- Literary source two: Rufinus on Christianization of Aksum -- Literary source three: Constantius's letters to Aksum and Alexandria -- Summary of literary sources -- The route: precedents -- Logistics and reconstructing the actual route -- Reconstruction of literary and logistical sources -- Perceptions of the Himyarites -- Perceptions of the Aksumites -- Perceptions of the Alexandrians -- Concluding perceptions of Constantius -- 3 Constantius's bishop management program -- Constantine's record on episcopal banishment -- Constantius forced to innovate by circumstances: Bishop Paul in Constantinople -- A first politically successful exile: Paulinus of Trier -- A western purge: Dionysius of Milan, Eusebius of Vercelli, and Lucifer of Cagliari -- New approaches to eliminating political enemies: Liberius of Rome, Hilary of Poitiers, Hosius of Corduba -- The staged deposition of Athanasius -- Non-Nicene episcopal exiles: Eudoxius, Basil, and Eustathius -- 4 Constantius's bureaucracy abroad -- Constantius's addressee Strategius Musonianus -- Constantius creates a network of agents in the 350s -- Speculation on the missions of these agents traveling to the Red Sea.